Real-Time Quaking-Induced Conversion Detection of Bovine Spongiform Encephalopathy Prions in a Subclinical Steer - Hwang, Soyoun; West Greenlee, M. Heather; Balkema-Buschmann, Anne; Groschup, Martin H.; Nicholson, Eric M.; Greenlee, Justin J. (Frontiers in Veterinary Science, 2018)
Bovine spongiform encephalopathy (BSE) belongs to a group of fatal prion diseases that result from the misfolding of the cellular prion protein (PrPC) into a pathogenic form (PrPSc) that accumulates in the brain. In vitro assays such as serial protein misfolding amplification and real-time quaking induced conversion (RT-QuIC) allow assessment of the conversion of PrPC to PrPSc. RT-QuIC can be used for the detection of prions in a variety of biological tissues from humans and animals. However, there is no such comparison of RT-QuIC data between BSE positive and pre-symptomatic cattle. Further, the current study assesses prion distribution in multiple brain regions of clinically ill or subclinical animals. Here, we compare RT-QuIC reactions seeded with brain samples collected from experimentally inoculated cattle that were clinically ill or subclinically affected with BSE. The results demonstrate RT-QuIC seeding in various brain regions of an animal with subclinical BSE despite being determined negative by immunohistochemistry. Bioassay of the subclinical animal and RT-QuIC of brainstem from inoculated knockout (PRNP -/-) cattle were used to confirm infectivity in the subclinical animal and determine that RT-QuIC reactions were not the result of residual inoculum, respectively. These results confirm that RT-QuIC is a highly sensitive prion detection assay that can detect prions in a steer prior to the onset of clinical signs of BSE.